THE KICHUA-LAMISTS: A FIELD EXPERIENCE - Calderón Pacheco, Luis (2000)
This paper has a double porpuse. One one hand, it describes and interprets the way in which a specific echnic group (the kichua-lamistas) creares, handles and reinvents its culture, showing at the same time, the difficulties chac emerges upon attempting this boarding. Addicionally, it cricicizes chose postures chat propuses that che existance of indigenious cultures is perjudicial for the development of a country. lt is relevant to indicates that che author uses a literary resource as form of expressing his cheoretical reflection. This position is evident in the vague mixture of realicy and ficcion. Besides imaginary characters as Marito, appears real individous thac inhabits in che Kichua-lamistas communities chat che researcher visiced.